Identifikasi Potensi Bahaya Keselamatan dan Kesehatan Kerja pada Proses Produksi di PT Kerinci Merangin Hidro (Pembangkit Listrik Tenaga Air) - Rahmi, Aprianti; Tanjung, Aman Soleh (Universitas Batanghari Jambi, 2024)
This research uses a qualitative approach with a focus on analyzing occupational safety and health risks in the production section at PT. Kerinci Merangin Hydro. The Occupational Safety and Health Management System implemented by PT Kerinci Merangin Hidro is considered appropriate for reducing the risk of work accidents. However, in implementation, not all employees support and comply with the regulations set by PT. Kerinci Merangin Hydro